Heterobicyclic inhibitors of transforming growth factor beta receptor I (TGFβRI). Issue 5 (1st March 2018) - Harikrishnan, Lalgudi S.; Warrier, Jayakumar; Tebben, Andrew J.; Tonukunuru, Gopikishan; Madduri, Sudhakara R.; Baligar, Vishweshwaraiah; Mannoori, Raju; Seshadri, Balaji; Rahaman, Hasibur; Arunachalam, P.N.; Dikundwar, Amol G.; Fink, Brian E.; et al.
Graphical abstract: Abstract: The TGFβ-TGFβR signaling pathway has been reported to play a protective role in the later stages of tumorigenesis via increasing immunosuppressive Treg cells and facilitating the epithelial to mesenchymal transition (EMT). Therefore, inhibition of TGFβR has the potential to enhance antitumor immunity. Herein we disclose the identification and optimization of novel heterobicyclic inhibitors of TGFβRI that demonstrate potent inhibition of SMAD phosphorylation. Application of structure-based drug design to the novel pyrrolotriazine chemotype resulted in improved binding affinity (Ki apparent = 0.14 nM), long residence time (T1/2  > 120 min) and significantly improved potency in the PSMAD cellular assay (IC50  = 24 nM). Several analogs inhibited phosphorylation of SMAD both in vitro and in vivo . Additionally, inhibition of TGFβ-stimulated phospho-SMAD was observed in primary human T cells.